Does Income Inequality Lead to Terrorism? - Tim Krieger; Daniel Meierrieks (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the effect of income inequality on terrorism for a sample of 114 countries between 1985 and 2012. We provide evidence, robust to various methodological changes (e.g., different dependent variables, instrumental-variable approaches), that higher levels of income inequality are associated with more terrorism. Consistent with relative deprivation theory, we argue that this effect is a direct consequence of frustration over the distribution of income within a society, resulting in terrorism to voice dissent and achieve a redistribution of wealth. Furthermore, we provide evidence of an indirect effect of inequality on terrorism, where inequality may also contribute to terrorism by leading to weaker institutions. Finally, we show that redistributional efforts can be effective in reducing inequality and, consequently, terrorist activity.
Keywords: D74; I38; O15; C36; 330; income inequality; terrorism; Gini coefficient; relative deprivation; redistribution